ChemInform Abstract: Silver‐Mediated Oxidative Vinylic C—H Bond Sulfenylation of Enamides with Disulfides. Issue 16 (April 2015) - Yang, Luo; Wen, Qing; Xiao, Fuhong; Deng, Guo‐Jun
Abstract A plausible non‐chain radical mechanism based on mechanistic studies is suggested for the title transformation.